Evaluation of the Implementation of Credit Restructuring during the Covid-19 Pandemic at Bank Mandiri Ternate Branch - Buamona, Fanti Farjrianti; Sirat, Abdul Hadi; Suwito (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to evaluate the implementation of credit restructuring by Bank Mandiri Ternate branch during the Covid-19 pandemic in 2020-2021 and analyse the inhibiting factors in its implementation. This research uses a descriptive qualitative method with a phenomenological approach. Primary data was obtained through observation, interviews, and documentation, while secondary data was obtained from searching related documents. This research involved three informants from BMCT and four informants who are KUM and KUR business actors associated with the credit restructuring programme. The results showed that the implementation of business credit restructuring at Bank Mandiri Ternate Branch was in accordance with OJK regulations and Bank Mandiri's internal policies related to handling non-performing loans due to the Covid-19 pandemic. Although inhibiting factors in the implementation of the restructuring programme were heard, customers did not feel it as an obstacle because they felt helped by the existence of this programme which helped relieve their financial burden. On the other hand, there are also obstacles felt by the bank, especially related to social distancing rules that affect the implementation of restructuring.